2015
DOI: 10.1515/rjr-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene meshes and other alloplastic implants for soft tissue and cartilage nasal reconstructive surgery – a literature review

Abstract: BACKGROUND. The reconstructive surgery is a domain in continuous research for new techniques and alloplastic materials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…In this procedure, three small (18 mm) polyethylene terephthalate rods are inserted in the soft palate mucosal layer sagittally, parallel to each other and spaced 2 mm apart to strengthen them by causing fibrosis and scarring through induction of reaction toward foreign bodies [17,19,20,36]. Research and clinical results have demonstrated that polyethylene terephthalate is a stable, biologically inert compound that is safe for use in humans, as it has been used for decades in other medical devices such as surgical sutures, mesh and vascular grafts [37][38][39][40][41]. In 2004 pillar implants received US FDA clearance to treat snoring and obstructive sleep apnea [42].…”
mentioning
confidence: 99%
“…In this procedure, three small (18 mm) polyethylene terephthalate rods are inserted in the soft palate mucosal layer sagittally, parallel to each other and spaced 2 mm apart to strengthen them by causing fibrosis and scarring through induction of reaction toward foreign bodies [17,19,20,36]. Research and clinical results have demonstrated that polyethylene terephthalate is a stable, biologically inert compound that is safe for use in humans, as it has been used for decades in other medical devices such as surgical sutures, mesh and vascular grafts [37][38][39][40][41]. In 2004 pillar implants received US FDA clearance to treat snoring and obstructive sleep apnea [42].…”
mentioning
confidence: 99%